The effect of online summary assessment and feedback system on the summary writing on 6th graders: The LSA-based technique. (April 2016) - Sung, Yao-Ting; Liao, Chia-Ning; Chang, Tao-Hsing; Chen, Chia-Lin; Chang, Kuo-En
Abstract: Studies on teaching of reading strategies have found that summarizing is of tremendous help to reading comprehension. However grading students' summary writings is laborious, but given the importance of summarizing, an effective summarizing learning module is important. This study developed an automatic summary assessment and feedback system based on Latent Semantic Analysis (LSA) to provide score, concept and semantic feedback, and then investigated the effects of concept and semantic feedback on the writing of summaries by students in the sixth grade. The design involved two between-subject factors: semantic feedback (with, without) and concept feedback (with, without). 120 sixth-grade students from an elementary school were recruited for the study, and then were randomly assigned to each group. The overall results demonstrated the effectiveness of the proposed system in improving the summary writing skills of students. The effects of semantic feedback and concept feedback were also discussed. Highlights: An automatic summary assessment and feedback system based on LSA is proposed. An experiment was conducted to investigate the effects of various feedback modules. The proposed system improved students' summary writing. The concept feedback improved students' summarization significantly.